2007
DOI: 10.1007/s11120-007-9132-x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll thermofluorescence and thermoluminescence as complementary tools for the study of temperature stress in plants

Abstract: The photosynthetic apparatus, especially the electron transport chain imbedded in the thylakoid membrane, is one of the main targets of cold and heat stress in plants. Prompt and delayed fluorescence emission originating from photosystem II have been used, most often separately, to monitor the changes induced in the photosynthetic membranes during progressive warming or cooling of a leaf sample. Thermofluorescence of F (0) and F (M) informs on the effects of heat on the chlorophyll antennae and the photochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 124 publications
0
35
0
2
Order By: Relevance
“…Such reversible effects may be quantified by the temperature inducing a 15% reduction of F v /F m , the dark-acclimated quantum yield of photochemistry (Epron, 1997b). Higher temperatures (above 40 • C) may involve direct damage to PSII photochemistry: PSII proteins may be denaturated and thylakoid membrane fluidity may increase to very high levels when temperature reaches critical values (Ducruet et al, 2007;Yordanov, 1992). This critical temperature for PSII functions may be assessed using chlorophyll a fluorescence records and by detecting the leaf temperature at the thermal breakpoint of ground level chlorophyll a fluorescence recorded under darkness (F 0 ), called critical temperature T c , (Bilger et al, 1984;Ducruet et al, 2007;Terzaghi et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such reversible effects may be quantified by the temperature inducing a 15% reduction of F v /F m , the dark-acclimated quantum yield of photochemistry (Epron, 1997b). Higher temperatures (above 40 • C) may involve direct damage to PSII photochemistry: PSII proteins may be denaturated and thylakoid membrane fluidity may increase to very high levels when temperature reaches critical values (Ducruet et al, 2007;Yordanov, 1992). This critical temperature for PSII functions may be assessed using chlorophyll a fluorescence records and by detecting the leaf temperature at the thermal breakpoint of ground level chlorophyll a fluorescence recorded under darkness (F 0 ), called critical temperature T c , (Bilger et al, 1984;Ducruet et al, 2007;Terzaghi et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Higher temperatures (above 40 • C) may involve direct damage to PSII photochemistry: PSII proteins may be denaturated and thylakoid membrane fluidity may increase to very high levels when temperature reaches critical values (Ducruet et al, 2007;Yordanov, 1992). This critical temperature for PSII functions may be assessed using chlorophyll a fluorescence records and by detecting the leaf temperature at the thermal breakpoint of ground level chlorophyll a fluorescence recorded under darkness (F 0 ), called critical temperature T c , (Bilger et al, 1984;Ducruet et al, 2007;Terzaghi et al, 1989). Increased F 0 denotes an inactivation of PS II reaction centres due to thylakoid instability and complex changes in PS II (Cajanek et al, 1998;Ducruet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…STL and HTL techniques have been applied in several in vitro toxicological studies, mainly using thylakoids and cell cultures (Ducruet et al, 2007). Using thylakoids isolated from leaves of greenhouse grown peas (Pisum sativum L.), Mohanty et al (1989) suggested that Cu (II) does not block electron flow between the primary and secondary quinonic electron acceptor but modifies the secondary quinonic acceptor site in such a way that it becomes unsuitable for further PSII photochemistry.…”
mentioning
confidence: 99%